Variation in injecting drug use behavior across different North-eastern States in India - Subrata Biswas; Piyali Ghosh; Debjit Chakraborty; Arvind Kumar; Sumit Aggarwal; Malay Kumar Saha (Wolters Kluwer Medknow Publications, 2020)
Prevalence of adult HIV infection in India is still high in certain North-eastern (NE) states, particularly among injecting drug users (IDUs). This study aims at exploring IDU behavior profile and their variation across the different states of NE region, India. Data were drawn from a population-based, cross-sectional survey of IDU in the integrated bio-behavioral surveillance from 2014 to 2015. A total of 4272 IDUs from four states (Manipur, Meghalaya, Mizoram, and Nagaland) aged ≥15 years were interviewed. Descriptive analysis was conducted to identify the variation in demographic and IDU behavior across four states. Youth predominance in Mizoram was evident by the mean age of initiation <18 years; 74% and 65% had the first exposure of any drug and injecting drug in <20 years. In Manipur and Nagaland, 60% and 49% of IDUs, respectively, were ≥30 years of age. These specific age groups may be targeted for IDU risk mitigation addressing the state-specific determinants.